Efeitos da administração da L-arginina, do exercício resistido e da L-arginina associada ao exercício resistido sobre a reatividade vascular da artéria mesentérica de ratos diabéticos - Silva, Tharciano Luiz Teixeira Braga da (2011)
Diabetes mellitus (DM) can be defined as a heterogeneous group of metabolic disorders characterized by hyperglycemia, resulting in dysfunction, ultimately, failure of various organs, especially the eyes, kidneys, nerves and vascular system. This study aimed to evaluate the effects of L-arginine (L-Arg), resistance exercise (RE) and the association between them on changes of endothelium-derived relaxing factor (EDRF) in isolated rings of superior mesenteric artery of diabetic rats induced by alloxan. Wistar rats (250-300g) were divided into 7 groups: Control (CON, n = 4), Electrically Stimulated (ES, n = 4), Trained Control (TC, n = 4), Sedentary Diabetic (SD, n = 5), L-arginine Diabetic (L-Arg + D, n = 5), Trained Diabetic (TD, n = 5) and L-arginine + Trained Diabetic (L-Arg + TD, n = 5). The animals diabetic groups received alloxan 2 weeks before the start of treatment protocols. The RE protocol consisted of 3 sets of 10 squats (Tamaki apparatus) with an intensity of 50% of one repetition maximum (1RM). Animals treated with L-Arg received 1.25 mg/ml daily in drinking water. At the end of 8 weeks, vessel relaxation endothelium-dependent was obtained in rings pre-contracted with L-phenylephrine (Phe, 10 mM) by addition of increasing concentrations and cumulative acetylcholine (ACh, 10-9 10-4 M). After this, concentration-response curves were constructed in control conditions or in the presence of inhibitors of nitric oxide sintetase (L-NAME), cyclo-oxygenase (INDO) and potassium channels blockers (TEA). The vessel relaxation induced by 10 ACh showed a significant reduction (p < 0.05) in the maximum response (Rmax) of SD compared with CON. Furthermore, we observed a significant reduction (p < 0.001) in sensitivity (pD2) (6.8 ± 0.12 to 6.2 ± 0.11) of L-Arg + D compared with the SD. In the presence of L-NAME the L-Arg + D showed a reduction (p < 0.001) of vessel relaxation compared to the SD. After addition of L-NAME + INDO, the LArg + TD showed a significant reduction (p < 0.001) in vessel relaxation compared with the SD. The presence of L-NAME + INDO + TEA, the TD and L-Arg + TD showed a significant reduction (p <0.001) of vessel relaxation compared with the SD. The results show that although there was no improvement in vessel relaxation induced by ACh, we observed a change in the participation of EDRF in all groups.